{Generation of C-1′ radicals through a $β$-(acyloxy)alkyl rearrangement in modified purine and pyrimidine nucleosides} - Gimisis, Thanasis; Ialongo, Giuseppina; Chatgilialoglu, Chryssostomos (Tetrahedron, 1998)
The synthesis of protected 1',2'-didehydro-2'-deoxyadenosines has been optimized by incorporating a phosphoranylidene protection of the adenine amine function. These unsaturated adenosines have served as substrates for the electrophilic iodopivaloyloxylation leading to new nucleosides modified at the anomeric position. Reaction of halopivaloates 10, 11 and 12 with tributyltin hydride generates indirectly C-1' radicals through a $β$- (acyloxy)alkyl rearrangement. Rate constants for these rearrangements have been measured by using free-radical clock methodology and comparison of these data with previous reported results provides structural information about the nature of this important class of radicals.